Corroboration of Academic Performance with Various Study Preferences Followed Among Future Medical Professionals of Universiti Sultan Zainal Abidin (UniSZA) - U.S. Mahadeva, Rao; Thant, Zin; Nordin, Simbak (2014)
Background of study: Every student has their own pattern and scheme of study to perform better in their exam. Aim: To investigate the most preferable time, habit, attitude, and pattern chosen by students (respondents) during their study time to excel in their examinations. Introduction: Sleep plays an imperative role in students' academic performance. Adequate sleep boosts the students memory and performance on the next day learning activities. A maximum of eight hours sleep is recommended for every student. Methodology: The respondents are the future medical professionals of Universiti Sultan Zainal Abidin (UniSZA) including both genders as well as pre-clinical and clinical medical students. Results and Interpretation: The following criterion were analysed through the questionnaire and were tabulated as per the details furnished. i.e. Study time. and habits desired by the respondents. types of interruptions, social behaviour. style of reading, preference of pattern of study chosen by the respondents during the time of study, and number of respondents seeks help from their lecturer(s) to clarify their doubts in the consecutive days. Conclusion: From this cross sectional study among future meducationists. it could be postulated that the academic progress depends on the schedule and lifestyle of the student. RJPT All right reserved.